2019
DOI: 10.1108/hff-01-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Forced convection in a double tube heat exchanger using nanofluids with constant and variable thermophysical properties

Abstract: Purpose This paper aims to study forced convection in a double tube heat exchanger using nanofluids with constant and variable thermophysical properties. Design/methodology/approach The cold fluid was distilled water flowing in the annulus and the hot fluid was aluminum oxide/water nanofluid which flows in the inner tube. Thermal cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Later, Bahmani et al carried out a study on forced convection in a double-tube heat exchanger using nanofluids with constant thermophysical properties, considering Reynolds numbers between 100 and 1500 and employing the finite volume method for solving the governing equations. They found that heat transfer rate could be enhanced by increasing the nanoparticle volume fraction and the Reynolds number [ 68 ]. Poongavanam et al experimentally performed research on heat transfer and pressure drop using nanofluid multiwalled carbon nanotubes (MWCNT–Solar glycol) in a double-pipe heat exchanger.…”
Section: Effects Of Nanofluid Characteristics On Heat Transfer Rate A...mentioning
confidence: 99%
“…Later, Bahmani et al carried out a study on forced convection in a double-tube heat exchanger using nanofluids with constant thermophysical properties, considering Reynolds numbers between 100 and 1500 and employing the finite volume method for solving the governing equations. They found that heat transfer rate could be enhanced by increasing the nanoparticle volume fraction and the Reynolds number [ 68 ]. Poongavanam et al experimentally performed research on heat transfer and pressure drop using nanofluid multiwalled carbon nanotubes (MWCNT–Solar glycol) in a double-pipe heat exchanger.…”
Section: Effects Of Nanofluid Characteristics On Heat Transfer Rate A...mentioning
confidence: 99%
“…The pressure-velocity equations were coupled together by implementing the SIMPLE (Semi Implicit Method for Pressure Linked Equations) algorithm [35,36], while the discretization of equations was defined by implementing the second-order upwind [37,38]. The residual criteria were set equal to 10 −7 for all equations to ensure the calculations' accuracy [33,39]. The turbulence was modeled using RNG k-ε.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…Tian et al [36] experimentally measured heat transfer in a silica DI water nano-fluid with three various surfactants on the surface of copper heaters at different concentrations at atmospheric pressure. Forced convection in a double-tube heat exchanger using nanofluids with constant and variable thermophysical properties was scrutinized by Bahman et al [37].…”
Section: Literature Surveymentioning
confidence: 99%